2020
DOI: 10.1002/aoc.5996
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties, structural, and DFT studies of Pd(II) complexes with 1‐phenyl‐1H‐tetrazol‐5‐thiol, X‐ray crystal structure of [Pd(κ1S‐ptt)2(κ2‐dppe)] complex

Abstract: Seven tetrazole‐thione complexes, [Pd2(κ2‐ptt)4](1), trans‐[Pd(k1‐S‐ptt)2(PPh3)2] (2), trans‐[Pd(k1‐S‐ptt)2(SPPh3)2] (3), trans‐[Pd(k1‐S‐ptt)2(OPPh3)2] (4), [Pd(k1‐N‐ptt)2(k2‐dppe)] (5a), [Pd(k1‐S‐ptt)2(k2‐dppe)] (5b), [Pd(k1‐S‐ptt)2(k2‐dppeS2)] (6), and [Pd(k1‐S‐ptt)2(k2‐dppeO2)] (7), were prepared from 1‐phenyl‐1H‐tetrazole‐5‐thiol (Hptt), with substituted phosphines. These complexes were investigated by CHNS analysis; infrared (IR), nuclear magnetic resonance (NMR) (1H and 31P), and ultraviolet–visible (UV–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The IR spectrum of the [PhHg(mtzS)] complex (Figure S15) displayed the disappearance (S‐H) vibration which showed in the spectrum of the free 5‐mercapto‐1‐methyltetrazole ligand (Figure S16) (appeared at 2607 cm −1 ), indicates to the deprotonated of the proton of the HmtzS ligand and formed an anion form (mtzS − ) and coordinates to the metal ion through the sulfur atom of the thiolate group 10‐14 . Also, the spectrum displayed a strong band 1572 cm −1 due to the ν(C=N) 10‐14 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The IR spectrum of the [PhHg(mtzS)] complex (Figure S15) displayed the disappearance (S‐H) vibration which showed in the spectrum of the free 5‐mercapto‐1‐methyltetrazole ligand (Figure S16) (appeared at 2607 cm −1 ), indicates to the deprotonated of the proton of the HmtzS ligand and formed an anion form (mtzS − ) and coordinates to the metal ion through the sulfur atom of the thiolate group 10‐14 . Also, the spectrum displayed a strong band 1572 cm −1 due to the ν(C=N) 10‐14 .…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][14] Also, the spectrum displayed a strong band 1572 cm À1 due to the ν(C=N). [10][11][12][13][14] The IR spectra of the complexes (2-7) (Figures S17-S20) displayed new bands within (1431-1435 cm À1 ) and (505-511 cm À1 ) due to the ν(Ph-P) and ν(P-C) the of the phosphine ligands, indicating their participation in complex formation. 33,36 The IR spectra of the complexes ( 8) and ( 9) displayed new bands within 1560 and 1589 cm À1 assigned to the ν(C=N) of the Bipy and Phen ligands, respectively, indicating their participation in complex formation, this band was shifted to lower frequency compared with free ligands, indicated that the amine were bonded through the nitrogen atom of the amine ligand.…”
Section: Ir Datamentioning
confidence: 98%
See 1 more Smart Citation
“…In our previous work, we reported the synthesis of transition and nontransition metal complexes of heterocyclic ligands such as tetrazole, dithiocarbamate, and oxime. [10,[24][25][26][27][28] In the present work, we describe the prepared phenolic aldoxime complexes with different metal ions with the study of nanoproperties; in addition, we examined for anticancer and antibacterial activity. Interestingly, different substitutes and spacer groups in the structure of ligand confer different electronic (space configuration, electron density distribution, and spectral), geometric, and biological properties of their metal complexes, which can be observed when computational studies are performed.…”
mentioning
confidence: 99%
“…In doing so, it forms a small bite angle (S-M-S), ranging from 65 to 80 being dependent upon the size of the ligand and metal ion (B); [7,9, (iii) bidentate bridging mode through the two sulfur atoms or through the one of the sulfur atom only (C); [26,37,[39][40][41] (iv) poly-dentate mode between three center or more (D). [28,37,[42][43][44] Metal complexes of dithiocarbamate present a wide range of applications in agricultural science, medicine as antibacterial, anti-fungal, and anti-inflammatory, industry, analytical, and organic chemistry. [1][2][3][4][5][6][7][8][9][10][11] In the present work, we describe the synthesis, characterization, and biological activity of Zn (II) and Pd (II) mixed ligand complexes of piperidine dithiocarbamate (PipDT) and amine ligands {2,2 0 -bipyridineine (Bipy), 1,10-phenanthroline (Phen), and 3-aminopyridine (3Apy)}, whereas the treatment of cis-[PdCl 2 (PPh 3 ) 2 ] with sodium benzisothiazolinate (Nabit) or sodium saccharinate (Nasac), followed by addition, sodium piperidine dithiocarbamate (NaPipDT) to give complexes of the type trans-…”
mentioning
confidence: 99%